Material Culture and the Social, Economic, Architectural, and Religious Transformations of Palestine during the Neolithic and Chalcolithic Periods: A Comprehensive Overview - Al-Houdalieh, Salah Hussein (Arab Journal for Sciences and Research Publishing, 2025)
This study explores the archaeological remains of Palestine from the Neolithic and Chalcolithic periods, based on excavations carried out over the past two centuries. The research aims to highlight how climate changes during these periods affected patterns and methods of subsistence, and to present the key intellectual and material achievements of each period within a streamlined narrative. This approach helps readers follow the developments in social structures, religious thought, economic systems, tools and pottery production, architectural styles, and burial customs along with their grave goods. The study uses a descriptive-analytical approach, reviewing relevant literature and conducting comparative analysis to arrive at the most accurate interpretations. Results show that the warmer climate in Palestine during the Neolithic and Chalcolithic periods played a major role in promoting permanent settlements, the creation of agricultural and craft villages, and significant lifestyle changes. The research also finds that people in these periods pioneered innovations that positively impacted their quality of life and influenced later societies—such as developing agriculture, domesticating animals, advancing various industries, and shaping religious beliefs.
Keywords: Neolithic period; Chalcolithic period; prehistory; Palestine; material culture; social transformation